Simple motor tasks independently predict extubation failure in critically ill neurological patients - Fernanda Machado Kutchak (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: To evaluate the usefulness of simple motor tasks such as hand grasping and tongue protrusion as predictors of extubation failure in critically ill neurological patients. Methods: This was a prospective cohort study conducted in the neurological ICU of a tertiary care hospital in the city of Porto Alegre, Brazil. Adult patients who had been intubated for neurological reasons and were eligible for weaning were included in the study. The ability of patients to perform simple motor tasks such as hand grasping and tongue protrusion was evaluated as a predictor of extubation failure. Data regarding duration of mechanical ventilation, length of ICU stay, length of hospital stay, mortality, and incidence of ventilator-associated pneumonia were collected. Results: A total of 132 intubated patients who had been receiving mechanical ventilation for at least 24 h and who passed a spontaneous breathing trial were included in the analysis. Logistic regression showed that patient inability to grasp the hand of the examiner (relative risk = 1.57; 95% CI: 1.01-2.44; p < 0.045) and protrude the tongue (relative risk = 6.84; 95% CI: 2.49-18.8; p < 0.001) were independent risk factors for extubation failure. Acute Physiology and Chronic Health Evaluation II scores (p = 0.02), Glasgow Coma Scale scores at extubation (p < 0.001), eye opening response (p = 0.001), MIP (p < 0.001), MEP (p = 0.006), and the rapid shallow breathing index (p = 0.03) were significantly different between the failed extubation and successful extubation groups. Conclusions: The inability to follow simple motor commands is predictive of extubation failure in critically ill neurological patients. Hand grasping and tongue protrusion on command might be quick and easy bedside tests to identify neurocritical care patients who are candidates for extubation.